Tribbles 3 Regulates the Fibrosis Cytokine TGF-β1 through ERK1/2-MAPK Signaling Pathway in Diabetic Nephropathy - Luwei Zhang; Jinhang Zhang; Xinnong Liu; Shengli Liu; Jun Tian (Journal of Immunology Research)
To reveal the expression and possible role of tribbles homolog 3 (TRB3) in the incidence of type 2 diabetic nephropathy, we used immunohistochemistry, real-time quantitative PCR, western blot analysis, and enzyme-linked immunosorbent assay (ELISA) to study the expression of TRB3, extracellular signal-regulated kinase 1/2 mitogen-activated protein kinase (ERK1/2 MAPK), transforming growth factor β1 (TGF-β1), and collagen type IV in kidneys of db/db diabetic mice and in murine renal mesangial cells stimulated with high glucose. The expression of TRB3, TGF-β1, and collagen type IV was increased in kidneys of db/db diabetic mice. TGF-β1 and collagen type IV regulated by high glucose through ERK1/2 MAPK were downregulated by silencing TRB3 in renal mesangial cells. TRB3 may be involved in diabetic nephropathy by regulating the fibrosis cytokine TGF-β1 and collagen type IV through the ERK1/2 MAPK signaling pathway.